State of the Science: Tools and Measurement for Shared Decision Making. (7th December 2016) - Sepucha, Karen R.; Breslin, Maggie; Graffeo, Charles; Carpenter, Christopher R.; Hess, Erik P.
Abstract: Shared decision making (SDM) has been advocated as an approach to selecting medical tests and treatments for many situations. The goal of SDM is to ensure that patients are well informed, are meaningfully involved in decisions, and receive treatments that meet their goals and preferences. There is considerable evidence about the tools used to promote SDM, called patient decision aids, and many different measures have been developed to assess the impact of SDM. However, fairly little is known about the applicability of the tools and measures in the emergency department (ED) setting. This article builds on insights from two keynote lectures presented at the 2016 Academic Emergency Medicine Consensus Conference discussing the state of the science for measurement of SDM and the design of patient decision aids to promote SDM conversations and highlights some key areas for further research to advance SDM in the ED.